Alterations in internetwork functional connectivity in patients with chronic migraine within the boundaries of the Triple Network Model. Issue 5 (27th June 2020) - Trufanov, Artem; Markin, Kirill; Frunza, Daria; Litvinenko, Igor; Odinak, Miroslav
Abstract: Background: Alterations in large‐scale functional connectivity have widely been used to understand migraine pathophysiology and to find any imaging markers. The successful use of the Triple Network Model for many mental and neurological diseases has prompted us to consider chronic migraine under the prism of this model for the first time in the literature. Aim: To evaluate alterations in functional connectivity between large‐scale networks using resting‐state fMRI in chronic migraine patients and their correlation with clinical features within the boundaries of the Triple Network Model. Methods: Twenty‐five chronic migraine patients underwent 1, 5T resting‐state functional magnetic resonance imaging (RS‐fMRI) scanning during the interictal phase and were compared to a group of 25 healthy controls. Functional connectivity was assessed using region‐of‐interest to region‐of‐interest (ROI‐to‐ROI) analysis between 8 networks and 15 subcortical areas, conventionally assigned to salience network. Results: Compare to healthy controls, patients had increased functional connectivity between salience network (SN) and sensorimotor network (SMN) and dorsal attention network (DAN), between nucleus accumbens and default mode network (DMN) and within DMN and also between thalamus and DAN. Decreased functional connectivity was registered between nucleus accumbens and DAN, and also within DAN. A higher depression scale score was positively correlated with an increase in FC within DMN. Conclusion: Taken together, our results show that patients with chronic migraine could be characterized by specific dysfunctional interactions between the SN, SMN, DAN, and DMN during resting state.